Answer: x=-2 Y=1
Step-by-step explanation: You convert the first equation to slope form then you take the second equation, so 3x+3y=-3 and you plug in the Y. So this would be 3x+3(-3/4-1/2)=-3. Then you would solve that equation and get the answer 3x-9/4x-3/2=-3. Now you combine like terms to get the answer 3/4x-3/2=-3 and you add 3/2 to both sides of the equation which leaves you with 3/4x=-3/2 now you solve for x and get -2. Now to find the y you take the first equation, that you converted to slope intercept form y=mx+b, and you plug in the x. Which would give you the problem, y=-3/4(-2)-1/2 then you get y=3/2-1/2 and you combine like terms to get the answer y=1